Initiating Interfaith Fiqh in the Modern Era: An Effort to Contextualize Rahmah and Humanist Islam in Digital Space - Azisi, Ali Mursyid; Amran, Najah Nadiah; Hasanah, Eva Putriya; Nurhalizah, Mevy Eka (Religió Jurnal Studi Agama-agama, 2023)
Abstract: The article reveals the crucial role of contextualizing fiqh as the foundation of Islamic law in addressing contemporary human challenges, with a particular focus on interfaith fiqh. In the modern era when societies are increasingly diverse and interconnected, it is imperative to adapt and advance Islamic legal principles to effectively address current issues and promote harmonious coexistence. This article uses library research as a data collection technique and theory of maslahah to discuss the subject. It argues that fiqh has the capacity to adjust to the demands of the contemporary era. Interreligious fiqh in Indonesia needs to get more attention, which will be a social landmark in the midst of social diversity. In essence, in sharia, Islamic principles promote mutual respect social control, deliberation, peace, pluralism, brotherhood, loving-kindness, equality, fairness, freedom, responsibility and honesty. Efforts that can be taken are: (1) practicing mutual forgiveness, (2) respecting human dignity, (3) being fair and creative in solving problems, and (4) formulating a peaceful civilization with a loving-kindness approach. Because digital space is the second place of socialization and has been a primary need for modern humans, by utilizing such social medias as Instagram, WhatsApp, websites, Facebook and other platforms, this article supports the socialization process of fiqh products which are inclusive, humanist and pluralist.